(untitled) (Baghdad Science Journal, 2020)
The emergence of staphylococci, either coagulase negative (CNS) or coagulase positive (CPS), as important human pathogens has implied that reliable methods for their identification are of large significance in understanding the diseases caused by them. The identification and characterization of staphylococci from biopsies taken from human breast tumors is reported here. Out of 32 tissue biopsies, a total of 12 suspected staphylococci grew on mannitol salt agar (MSA) medium, including 7 fermenters and 5 non-fermenter staphylococci based on traditional laboratory methods. Polymerase chain reaction (PCR) successfully identified seven isolates at the genus level as methicillin resistant Staphylococcus spp. by targeting a common region of the mecA gene. Only two of the seven bacteria were S. aureus based on the three-specific primers designed to amplify the housekeeping gene recN, and two of the virulence genes icaD and pvl. Diagnosing the isolates using the Vitek system revealed different findings. Although 6 of 7 isolates belonged to the Staphylococcus genus, including: S. cohnii subsp. cohnii, 2 isolates; S. lentus, 2 isolates; and one isolate for each S. auricularis and S. xylosus, the last bacterium was completely different (Aerococcus viridans). Concerning the two bacteria characterised as S. aureus by PCR, they were identified as S. lentus by Vitek with comparatively low detection probabilities of 93% and 88%. The data of this study indicate that undoubtedly PCR is a reliable and accurate test for identification of mannitol fermenter and salt tolerant bacteria in comparison with other tests that depend mainly on biochemical characteristics.